Representasi Sifat Kikir dalam Legenda Awal Mula Babakan Aso, Kabupaten Purwakarta, Jawa Barat, Indonesia - Setiawan, Janten Hidayat; Harini, Yostiani Noor Asmi; Durachman, Memen (Jurnal Bahastra, 2025)
This study aims to reveal the representation of miserliness as depicted in the local legend "Awal Mula Babakan Aso Hese Cai" from the Purwakarta region. Employing a qualitative method, the research analyzes the legend’s structure, narrative context, function, and meaning through Todorov’s narrative theory (1975). Data were collected through interviews with local informants and analyzed to uncover the socio-cultural dimensions embedded within the legend. The findings indicate that the miserly character is portrayed negatively, with miserliness presented as a destructive trait that ultimately leads to punishment—in this case, the disappearance of lake water. The legend is deeply rooted in the cultural and oral traditions of Purwakarta, shaped by existing local narratives and transmitted through generations via oral storytelling. Its primary function is didactic, emphasizing moral values and promoting the importance of generosity over selfishness. The meaning embedded within the legend suggests that greed leads to social and environmental consequences, whereas sharing is a virtue upheld by the community. Thus, the legend serves not only as a narrative artifact but also as a reflection of local wisdom and collective moral consciousness.